Development of antibacterial, degradable and ph-responsive chitosan/guar gum/polyvinyl alcohol blended hydrogels for wound dressing - Khan M.U.A.; Iqbal I.; Ansari M.N.M.; Razak S.I.A.; Raza M.A.; Sajjad A.; Jabeen F.; Mohamad M.R.; Jusoh N. (MDPI, 2023)
antiinfective agent; chitosan; galactan; guar gum; mannan; plant gum; polyvinyl alcohol; administration and dosage; bacterium; bandage; chemistry; drug effect; drug release; hydrogel; wound healing; Anti-Bacterial Agents; Bacteria; Bandages; Chitosan; Drug Liberation; Galactans; Hydrogels; Mannans; Plant Gums; Polyvinyl Alcohol; Wound Healing